EFFECT OF SPERM CAPACITATION MEDIA ON IN VITRO FERTILIZATION OF ARABI EWES OOCYTES - Taha .J . Al-Taha (Mesopotamia Journal of Agriculture)
The study was conducted at Assisted Reproductive Technology Center (A R T) College of Medicine, University of Basra , from January , 2009 to January ,2010 . The aim was to study the effect of capacitation media on in vitro fertilization of Arabi ewes oocytes . A total of 2279 oocytes were collected from ovaries obtained from Basra Slaughter House .Oocytes were matured in TCM199 (tissue culture medium 199) supplemented with10%Fetal bovin serum (FBS) to study the effect of capacitation media on their fertilizing ability. freshly ejaculated and frozen thawed spermatozoa were capacitated in 1 of 2 media .A Bracket culture medium or Earle’s balanced salt medium . Results revealed that Bracket medium with Hyalouronidase enzyme and Gentamycin instead of Penicillin antibiotics showed significant increase (P≤ 0.05) in number of in vitro fertilized and divided ewe’s oocytes as compared with the Earle’s in both fresh and frozen thawed spermatozoa .